Environmental Goods A Comparison of the APEC and OECD Lists - Steenblik, Ronald (OECD Trade and Environment Working Papers, 2005)
This paper compares two lists of environmental goods that have been used in the WTO negotiations on liberalising trade in environmental goods and services. It describes the genesis of the lists, which were compiled in the late 1990s. The OECD list was developed as a basis for analysing trade and tariffs. The APEC list emerged from nominations by member economies of the Asia-Pacific Economic Co-operation forum, as part of an effort to attain early voluntary liberalisation of trade in particular sectors. The concluding section of the chapter identifies common elements in the two lists and explains important differences